Ooutsourcing and ionizing radiation overexposure in applicants to minin services labor - Ramírez, Augusto (2002)
Objective: To determine the number of applicant examinations taken in one year and quantify the number of thoracic X-rays subjected. Design: Prospective descriptive study. Material and methods: In 400 applicants to work by the modality of services in the Peruvian mining the quantity of applicant exams taken in the previous immediate year to the current examination and the number of chest X-rays in a year were determined. It also verifies additional X-ray exposition due to diagnostic exams derived from accidents or diseases and the quantity of natural ionized radiation received from open pit and high altitude work. Results: Forty-five per cent of men examined take one applicant work examination per year, 29% two, 12% three, 13% between four and six and in 5 applicants seven applicant work exams were taken during the year. By calculating the annual weighted equivalent accumulative dose of ionizing radiation an average of 169 mRem/ year was found, with a total weighted risk to develop cancer of 289 x 10-6 examinations. Conclusion: To limit the number of applicant work examinations in this outsourcing work modality is recommended.